Ab initio study of adsorption and diffusion of lithium on transition metal dichalcogenide monolayers - Sun, Xiaoli; Wang, Zhiguo (Beilstein Journal of Nanotechnology, 2017)
Using first principles calculations, we studied the stability and electronic properties of transition metal dichalcogenide monolayers of the type MX2 (M = Ti, Zr, Hf, V, Nb, Ta, Mo, Cr, W; X= S, Se, Te). The adsorption and diffusion of lithium on the stable MX2 phase was also investigated for potential application as an anode for lithium ion batteries. Some of these compounds were found to be stable in the 2H phase and some are in the 1T or 1T' phase, but only a few of them were stable in both 2H/1T or 2H/1T' phases. The results show that lithium is energetically favourable for adsorption on MX2 monolayers, which can be semiconductors with a narrow bandgap and metallic materials. Lithium cannot be adsorbed onto 2H-WS2 and 2H-WSe2, which have large bandgaps of 1.66 and 1.96 eV, respectively. The diffusion energy barrier is in the range between 0.17 and 0.64 eV for lithium on MX2 monolayers, while for most of the materials it was found to be around 0.25 eV. Therefore, this work illustrated that most of the MX2 monolayers explored in this work can be used as promising anode materials for lithium ion batteries.
Keywords: anode materials; lithium adsorption; lithium diffusion; lithium ion batteries; transition metal dichalcogenide